Long-term weight-loss in gastric bypass patients carrying melanocortin 4 receptor variants. - Bryn S Moore (PLoS ONE, 2014)
The melanocortin 4 receptor (MC4R) critically regulates feeding and satiety. Rare variants in MC4R are predominantly found in obese individuals. Though some rare variants in MC4R discovered in patients have defects in localization, ligand binding and signaling to cAMP, many have no recognized defects.In our cohort of 1433 obese subjects that underwent Roux-en-Y Gastric Bypass (RYGB) surgery, we found fifteen variants of MC4R. We matched rare variant carriers to patients with the MC4R reference alleles for gender, age, starting BMI and T2D to determine the variant effect on weight-loss post-RYGB. In vitro, we determined expression of mutant receptors by ELISA and western blot, and cAMP production by microscopy.While carrying a rare MC4R allele is associated with obesity, carriers of rare variants exhibited comparable weight-loss after RYGB to non-carriers. However, subjects carrying three of these variants, V95I, I137T or L250Q, lost less weight after surgery. In vitro, the R305Q mutation caused a defect in cell surface expression while only the I137T and C326R mutations showed impaired cAMP signaling. Despite these apparent differences, there was no correlation between in vitro signaling and pre- or post-surgery clinical phenotype.These data suggest that subtle differences in receptor signaling conferred by rare MC4R variants combined with additional factors predispose carriers to obesity. In the absence of complete MC4R deficiency, these differences can be overcome by the powerful weight-reducing effects of bariatric surgery. In a complex disorder such as obesity, genetic variants that cause subtle defects that have cumulative effects can be overcome after appropriate clinical intervention.